Personnel protection : vehicle operations and safety ; proven practices - Miller, Jerome; Jones, Radford (Elsevier, 2014)
Personnel Protection: Vehicle Operations and Safety is a video presentation. Length: 20 minutes. Because a business executive typically spends a considerable amount of time travelling by vehicle, the greatest risk of injury or death to the executive is by vehicle accident or attack while in the vehicle. In Personnel Protection: Vehicle Operations and Safety, presenters Jerome Miller and Radford Jones discuss the basic security principles of executive driver safety and training. This 20-minute video presentation of narrated slides covers the challenges the executive driver may face, how and.